A Comparative Study Between Google Application and Oxford Dictionary in EFL Learners’ Pronunciation - Rauhil Hamdini; Baiq Suprapti Handini; Selamet Riadi Jaelani (LPPM Universitas Bumigora Mataram, 2022)
The aim of this study was to determine the significant differences in the use of the Google Application and the Oxford Dictionary Application on the pronunciation results of the second-semester students in Hamzanwadi University English Study Program. The method used in this research is the comparative method. The population used in this study were second-semester students of the English education study program, totaling 125 students, and 32 students participating as samples. The instrument of this research is an oral test. The data collection technique was using a pronunciation test. The result of this research shows that there is a significant difference in their pronunciation mastery between using Google Application and Oxford Dictionary. It was found that the result of the mean score of the students using Google Apps was 72.75 and the standard deviation was 6.92. It means that the pronunciation mastery of the students in using Google Apps belongs to the